Assessment of seawater intrusion based on geochemical and isotopic data in Makassar coastal area, South Sulawesi, Indonesia - Nugroho, Sunu Ardhi; Wilopo, Wahyu; Taufiq, Ahmad (Journal of Degraded and Mining Lands Management, 2024)
Makassar coastal area has experienced rapid development and has shown various negative impacts from groundwater overexploitation, such as seawater intrusion. This study aimed to assess seawater intrusion based on geochemical and isotopic data in the Makassar coastal area. The research was carried out by field measurement and taking the groundwater samples to the laboratory for geochemical and isotope tests. Geochemical analysis of seawater intrusion was based on TDS, EC, Cl-, Simpson ratio, Ca enrichment, BEX, Na/Cl ratio, and the piper trilinear diagram typer of water. Isotope analysis of seawater intrusion is based on comparing oxygen and deuterium isotopic data from groundwater samples with seawater, river, and rainwater. The results showed that some areas near the sea indicated seawater intrusion in both the semi-unconfined and unconfined aquifers. The indicated seawater intrusion spread in the north Tallo, Mamajang, and Tamalate subdistricts.